Analysis of MMP-9 and TIMP-2 gene promoter polymorphisms in individuals with hypodontia - Peres,Regina C.R. (2005)
Hypodontia, the congenital absence of one or a few teeth, is one of the most common developmental alterations of human dentition. It may cause masticatory and speech dysfunctions and create esthetic problems with orthodontic and prosthetic implications. MMP-9 is an important member of the matrix metalloproteinase (MMP) family that participates in remodeling of extracellular matrix during tooth development. A C-to-T base exchange at position -1562 creates two different alleles, and the CT and TT genotypes promote high activity of the MMP-9 gene promoter. Tissue inhibitor of metalloproteinase-2 (TIMP-2) regulates the activity of MMPs in the extracellular matrix and is co-expressed with gelatinases A (MMP-2) and B (MMP-9) during mouse tooth morphogenesis. A polymorphism in the TIMP-2 gene promoter at position -418 has been found in a Sp-1 binding site. In this study, the association between these DNA polymorphisms and hypodontia has been investigated. The significance of differences in frequencies of polymorphisms in control and test groups was assessed by Chi-square test (p<0.05). Data suggested that MMP-9 gene promoter polymorphism was not associated with hypodontia. The high frequency of GG genotype in the TIMP-2 gene promoter showed that this site was unsuitable for studies of DNA polymorphism-disease associations in the studied population.